Pourquoi être résilient quand on est efficace ? - Christine Bouisset; Simon Vanneufville (VertigO, 2018)
This paper aims at studying the use of the concept of resilience to analyze forest fires management in the Landes of Gascony (Southwest France). Resilience is defined as the capacity of a social system to ensure its sustainability by accompanying change. However, the Landes forest has experienced many disasters, particularly major fires in the 1940s. This episode led to an original risk management system. Since its creation, this system, based on forest equipment and rapid intervention by firefighters, seems very effective. However, it does address symptoms and not the causes of fires. In addition, the territorial context of the region is undergoing deep changes with significant peri-urbanisation, which is a source of increased vulnerability. Based on a qualitative survey of semi-directive interviewswe show that resilience is not, fundamentally, the objective to be retained for practitioners. On the contrary, for a large majority, the efficiency of risk management justifies not taking territorial changes into account.